The p38-MITOGEN-ACTIVATED PROTEIN KINASE Signaling Pathway Is Involved in Leonurus artemisia Extract-Induced Inhibition of the Proliferation of Human Bladder Cancer BFTC-905 Cells via G1/G0 Arrest and Causes Apoptosis In Vitro - Jian-Hui Lin; Chein-Hui Hung; Yun-Ching Huang; Chih-Shou Chen; Dong-Ru Ho (MDPI AG, 2023)
Bladder cancer is a urothelial malignancy. Bladder cancer starts in the urothelial cells lining the inside of the bladder. The 5-year recurrence rate for bladder cancer ranges from 31% to 78%, and the progression rate is approximately 45%. To treat bladder cancer, intravesical drug therapy is often used. Leonurus artemisia extract (LaE) was obtained from medicinal samples of Chinese motherwort Scientific Chinese Medicine; L. artemisia has various biological effects. This study investigated the impact of LaE on human bladder cancer cells (the BFTC-905 cell line) and the molecular mechanism underlying apoptosis resulting from the activation of cell signal transduction pathways in bladder cancer cells. A cell counting kit-8 (CCK-8) assay was used to determine the effect of LaE on cell growth. The effect of LaE on migration ability was observed using a wound healing assay. The effects of LaE on the cell cycle, reactive oxygen species production, and apoptosis were investigated. Western blot analysis detected apoptosis-related and mitogen-activated protein kinase signaling pathway-related protein concentrations. At non-toxic concentrations, LaE inhibited the proliferation of BFTC-905 cells in a concentration-dependent manner, and the half-maximal inhibitory concentration (IC50) was 24.08172 µg/µL. LaE impaired the migration ability of BFTC-905 cells. LaE arrested the cell cycle in the G1 and G0 phases, increased reactive oxygen species production, and induced apoptosis. LaE increased Bax and p-ERK concentrations and decreased Bcl-2, cleaved caspase-3, and p-p38 concentrations. No differences in PARP, C-PARP, vimentin, e-cadherin, p-JNK, or TNF-alpha concentrations were observed. These results suggest that LaE inhibits the proliferation of human bladder cancer cells. Moreover, the mitogen-activated protein kinase signaling pathway is involved in the inhibition of the proliferation of BFTC-905 cells.